PENGARUH MEDIA MAGIC BOX (KOTAK MISTERI) TERHADAP KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN - Amelia Fatmawati; Hendra Sofyan; Uswatul Hasni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language development is an important aspect of early childhood development because it supports children’s ability to communicate, express ideas, and interact with their social environment. However, in learning practices, some children still experience limitations in language abilities due to the lack of engaging and interactive learning media. This study aims to examine the effect of the Magic Box (Mystery Box) media on the language skills of children aged 5–6 years at TK Negeri 54 Talang Bukit. This research employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The research sample consisted of 24 children divided into two groups: 12 children in the experimental group and 12 children in the control group. Data were collected using an observation sheet containing 15 indicators of children's language skills. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using an independent sample t-test. The results showed that the average language skill score in the experimental group increased from 27.91 to 48.5, while the control group increased from 24.58 to 27.5. The hypothesis test indicated that t-count (6.584) > t-table (1.717) at a significance level of 0.05 with an effect size of 2.79, categorized as a strong effect. These findings indicate that the Magic Box media is effective in improving early childhood language skills through interactive and enjoyable learning activities.